From spatial data to spatial knowledge infrastructure: A proposed architecture - Ivanova, Ivana; Siao Him Fa, Jeremy; McMeekin, David; Arnold, Lesley; Deakin, R.; Wilson, M. (2020)
© 2020 John Wiley & Sons Ltd